Microbiological evaluation of inspected and non-inspected fresh sausages by the dry sheet medium culture plate method - Moraes, Gustavo Nunes de; Camargo, Gabriel Corrêa de; Alves Santomauro, Rafael; Sampaio, Aryele Nunes da Cruz Encide; Cerqueira-Cézar, Camila Koutsodontis; Caron, Evelyn Fernanda Flores; Possebon, Fábio Sossai; Pereira, Juliano Gonçalves; Martins, Otávio Augusto (Food Science and Technology, 2025)
Fresh sausage is the most consumed type of sausage in Brazil, owing to its high consumer acceptance and low cost. Despite its popularity, it can pose public health risks if contaminated with pathogens. This study aimed to evaluate the microbiological quality of inspected and non-inspected fresh sausages sold in the region of Bauru, São Paulo, Brazil. A total of 40 samples (30 inspected and 10 non-inspected) were analyzed using the dry sheet medium culture plate method (Compact Dry®) to detect Listeria monocytogenes, Salmonella spp., Staphylococcus aureus, Escherichia coli, and total coliforms, according to the manufacturer’s instructions. The results indicated a high level of contamination, particularly by Salmonella spp. (8/40, 20.00%) and L. monocytogenes (5/40, 12.50%). These findings highlight the need for stricter inspection procedures by regulatory agencies in the interior regions of São Paulo.